AI-Integrated E-Module Designed with the ADDIE Model to Enhance Critical Thinking and IPAS Competency in Indonesian Elementary Classrooms - Novi Ayuningtias Widianti; Sudarmiani Sudarmiani (AL-ISHLAH: Jurnal Pendidikan, 2026)
The limited development of critical thinking skills and suboptimal learning outcomes in Ilmu Pengetahuan Alam dan Sosial (IPAS) remain persistent challenges in Indonesian elementary education, largely due to teacher-centered instructional practices that restrict student engagement and reflective reasoning. This study aimed to develop and evaluate an AI-integrated e-module to enhance students’ critical thinking and IPAS competency. This research employed a development approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The e-module incorporated AI-based features, including automated feedback, personalized content adaptation, and voice-interactive tutoring. Validation involved experts in content, language, and media. Effectiveness was assessed a quasi-experimental one-group pretest–posttest design, with data analyzed using t-tests, N-Gain, and effect size measures.Expert validation indicated that the e-module was highly feasible and practical, achieving validity and practicality scores of 97% and 94%, respectively. Students demonstrated significant improvements in critical thinking skills (t = 5.784, p 0.001), with a high N-Gain of 0.80 and a large effect size (1.25). IPAS learning outcomes also showed notable enhancement.The findings confirm that AI-driven personalization and automated feedback effectively improve students’ analytical reasoning and conceptual understanding. The developed e-module is valid, practical, and effective for elementary education. Furthermore, this study contributes to the literature by proposing an ADDIE–AI hybrid model, addressing the limited integration of systematic instructional design and adaptive AI in Indonesian elementary learning contexts.